Locally Filtered Transport for computational efficiency in multi-component advection-reaction models. (April 2018) - Hajduk, Hennes; Hodges, Ben R.; Aizinger, Vadym; Reuter, Balthasar
Abstract: This work introduces the Locally Filtered Transport (LFT) method for numerical transport models. Locally turning off the transport computation in areas of nearly uniform concentration is proposed as a new approach for reducing computational cost in ecosystem models that require transport of tens to hundreds of constituent concentrations. The proposed method is locally mass conservative just as the discontinuous Galerkin finite element scheme it is based on. The performance of the method is illustrated using numerical examples including an advection-reaction ecosystem simulation with a simple nitrogen, phytoplankton, and zooplankton (NPZ) model. Highlights: Locally-filtered transport (LFT) method which solves scalar advection only where significant. Mass-conservative transport using only isolated sections of domain. New method applied for transport with Discontinuous Galerkin shallow water hydrodynamic solver. Simple cases are examined with results indicating that LFT has the potential to save computational time for large multi-species aquatic ecosystem simulations.